(untitled) (Mustansiria Dental Journal, 2018)
The dental pulp is a delicate connective tissue , it react to bacterial infection or to other stimuli by an inflammatory response .Once infection has been established in the pulp , spread of the process can be through the root canals and into the periapical lesions. The aim of this study was to evaluate the accuracy of digital and film panoramic radiographs in detection the periapical bone lesion in different sites ,which detected previously by periapical radiographs .In this study 106 teeth were examined by intra oral periapical radiographs which indicated that only 60 teeth were with periapical bone lesion , then by both digital and film panoramic the teeth with periapical lesion were examined .The results show significant advantage of digital panoramic which show the same mean of periapical lesion like conventional periapical radiographs , also the study show significant differences between digital and film panoramic radiographs in incisor region for the detection of periapical bone lesion .